2021
DOI: 10.1007/s10120-021-01202-8
|View full text |Cite|
|
Sign up to set email alerts
|

Propionibacterium acnes overabundance in gastric cancer promote M2 polarization of macrophages via a TLR4/PI3K/Akt signaling

Abstract: Objective Eradication of Helicobacter pylori (H. pylori) could not completely prevent the progression of gastric cancer (GC), suggesting that non-H. pylori bacteria may participate in the carcinogenesis of GC. The dysbiosis of microbiota in the stomach of GC has gradually been investigated, while the detailed mechanism that promotes GC in this process has not been elucidated. We aimed to identify a non-H. pylori bacteria that contribute to GC. Design GC tissues and adjacent normal tissues were collected to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 47 publications
1
32
1
Order By: Relevance
“…These genes, CCL17 , CCL18 , and PD-L1 , are mainly expressed in M2 macrophages, indicating that C. acnes is able to polarize the macrophage into an immunosuppressive M2 phenotype with the ability to recruit Tregs ( 15 ). In line with our results, a recently published study on gastric cancer identified C. acnes as a possible cause of increased polarization of macrophages against an M2 phenotype and increased cancer progression ( 31 ). Our microscopic examination of the macrophages stimulated with C. acnes revealed a rounder shape with a foamy appearance, as previously demonstrated in M2 macrophages with PD-L1 expression ( 32 ).…”
Section: Discussionsupporting
confidence: 92%
“…These genes, CCL17 , CCL18 , and PD-L1 , are mainly expressed in M2 macrophages, indicating that C. acnes is able to polarize the macrophage into an immunosuppressive M2 phenotype with the ability to recruit Tregs ( 15 ). In line with our results, a recently published study on gastric cancer identified C. acnes as a possible cause of increased polarization of macrophages against an M2 phenotype and increased cancer progression ( 31 ). Our microscopic examination of the macrophages stimulated with C. acnes revealed a rounder shape with a foamy appearance, as previously demonstrated in M2 macrophages with PD-L1 expression ( 32 ).…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that ECRG4 interacted with TLR4 [ 36 ]. And TLR4/PI3K/Akt signaling was a vital way to promote M2 polarization of macrophages [ 10 ]. Our results exhibited C2orf40/ ECRG4 expression notably related to immune cell infiltration, including M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the latest studies have proved that macrophages, mostly M2 polarized macrophages, have a vital role in the GC advance [ 9 , 10 ]. Infiltration of M2 macrophage might be a worthwhile biomarker for GC prognosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of Propionibacterium acnes is significantly increased in GC tissues and is related to TNM stages of GC patients. P. acnes induces M2 polarization of macrophages through TLR4/PI3K/Akt signaling to promote progression of GC (132). The crosstalk between macrophages and GC cells or other immune cells contributes to shaping the immunosuppressive microenvironment and to GC progression (133)(134)(135).…”
Section: Macrophagementioning
confidence: 99%